PENGARUH PERSEPSI SISWA ATAS MEDIA BELAJAR DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR EKONOMI - Nurlaela Nurlaela (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract: The purpose of this study is to determine the extent to which the influence of students' perceptions of learning media and achievement motivation on economic learning achievement. The research method used is survey with correlation and regression analysis, that is connecting between data showing student perception on learning media and achievement motivation owned by students with data showing student achievement in economic lesson. Hypothesis test results obtained by the following conclusions: (1) There is a significant influence of students' perceptions of learning media and achievement motivation jointly on the economic learning achievement of private vocational students in Depok City. It can be proved by the value of Sig = 0.000 <0,05 and Fhitung = 27, 823. (2) There is a significant influence of students' perceptions of the learning media on the economic learning achievement of private vocational students in Depok City. It can be proven by Sig = 0,000 <0,05 and tcal = 4,533. (3) There is a significant influence of achievement motivation on the economic learning achievement of private vocational students in Depok City. It can be proven by Sig = 0,000 <0,05 and tcal = 5,731.